Effect of FOLFIRINOX as second-line chemotherapy for metastatic pancreatic cancer after gemcitabine-based chemotherapy failure. Issue 19 (May 2017) - Kobayashi, Noritoshi; Shimamura, Takeshi; Tokuhisa, Motohiko; Goto, Ayumu; Endo, Itaru; Ichikawa, Yasushi
Abstract: Background: This study aimed to determine the maximum tolerated dose (MTD), dose-limiting toxicity, and efficacy of second-line chemotherapy with FOLFIRINOX after gemcitabine (GEM)-based chemotherapy failure in metastatic pancreatic cancer (MPC). Methods: We studied 18 histopathologically proven MPC patients. The schedule was 85 mg/m 2 oxaliplatin, irinotecan, and 400 mg/m 2 leucovorin, followed by 400 mg/m 2 5-fluorouracil (5-FU) as a bolus on day 1 and 2400 mg/m 2 5-FU as a 46-hour continuous infusion biweekly. The dose of irinotecan was defined as follows: level 0: 100 mg/m 2, level 1: 125 mg/m 2, level 2: 150 mg/m 2, and level 3: 180 mg/m 2 . The doses of other drugs were fixed. The primary endpoint of phase II study was the response rate (RR). Results: We initially evaluated 6 patients in a phase I study. One patient developed neutropenia and 1 patient developed hyperglycemia and severe infection. Accordingly, level 1 was chosen as the MTD. According to a phase II study, the RR was 22.2% and the disease control rate was 61.1%. The progression-free survival and overall survival were 2.8 (range, 0.7–19.1) and 9.8 (2.4–19.8) months, respectively. The most common severe adverse event was neutropenia (66.7%). Febrile neutropenia occurred in 1 (5.6%) case. Conclusion: The recommended dose was 85 mg/m 2 oxaliplatin, 100 mg/m 2 irinotecan, and 400 mg/m 2 leucovorin, followed by 400 mg/m 2 5-FU as a bolus on day 1 and 2400 mg/m 2 5-FU as a 46-hour continuous infusion. These results indicate that second-line FOLFIRINOX is a marginally effective treatment for GEM-based chemotherapy failure cases.